Celso Furtado: Tensions and Contradictions about the manpower problem in his classical book Economic Formation of Brazil - Sampaio, Elias Oliveira (Nexos Econômicos, 2019)
The article discusses the issue of manpower in the classical book Economic Formation of Brazil of Celso Furtado. The goal is to demonstrate that despite the importance of the classical text to understanding the process of building of country´s economy, the content and sequencing of Furtado’s arguments to explain the process of Brazilian underdevelopment in the first half of 1900s should be reviewed conceptually, analytically and theoretically due some tensions and contradictions observed on his own text, specifically, when he argues the reasons for the exclusion of the former slave – and their descendants – in the development of the Brazilian economy over in that period. Our main argument in this paper is that based in a formulation with an apparent neutral economic logic, the analytical construction of Furtado disregarded the importance of racial prejudice process that had undergone the former slaves to be included in the labor market at the time of transition from the slave labor to paid labor. Thus, he articulated the incorrect understanding that such exclusion was due, mainly per the lack of proper economic rationality of former slaves in front of the new relations established in the labor market in the coffee´s new company after the slavery and not because of the deep complexity that overwhelmed the whole Brazilian economy and particularly the paradigmatic changes in the labor market in the country since that time.